Accumulation of anthocyanins in tomato skin extends shelf life. Issue 3 (18th September 2013) - Bassolino, Laura; Zhang, Yang; Schoonbeek, Henk‐jan; Kiferle, Claudia; Perata, Pierdomenico; Martin, Cathie
Summary: Shelf life is one of the most important traits for the tomato ( Solanum lycopersicum ) industry. Two key factors, post‐harvest over‐ripening and susceptibility to post‐harvest pathogen infection, determine tomato shelf life. Anthocyanins accumulate in the skin of Aft/Aft atv/atv tomatoes, the result of introgressing alleles affecting anthocyanin biosynthesis in fruit from two wild relatives of tomato, which results in extended fruit shelf life. Compared with ordinary, anthocyanin‐less tomatoes, the fruits of Aft/Aft atv/atv keep longer during storage and are less susceptible to Botrytis cinerea, a major tomato pathogen, post‐harvest. Using genetically modified tomatoes over‐producing anthocyanins, we confirmed that skin‐specific accumulation of anthocyanins in tomato is sufficient to reduce the susceptibility of fruit to Botrytis cinerea . Our data indicate that accumulation of anthocyanins in tomato fruit, achieved either by traditional breeding or genetic engineering can be an effective way to extend tomato shelf life.